Parallel algorithm for calculating the integration. - Ehab Alasadi (المجلة العراقية للعلوم الاحصائية, 2025)
Analysis and implementation of a parallel algorithm to calculate the integration of the function y=1/e to the x with a specified time interval. Design and implementation using C/C++ is based on the sharing of memory among "THREADS." The "Pthread" library has been used. Use of the output file to print information and the purpose of using the POSIX library It is to implement the program faster than the one nucleus, when it involves a set of processors (THREADS) where each thread is considered to be a processor. This accelerates the solution of the complex problems in the system that need a large memory, where time sharing is used by Mutex. Lock and unlock through research prior to the use of parallel programs and its memory sharing technique to solve complex and large issues that require a long time to be implemented. Using parallel programs, each thread carries a particular issue and solves it, and the results are combined by reducing the time execution and increasing the speed of the system speedup according to the speed equation S=T1/Tn